Growth Differentiation Factor-15 Is Associated With Congestion-Related Anorexia and Weight Loss in Advanced Heart Failure - Monzo, Luca; Jarolim, Petr; Borlaug, Barry A; Benes, Jan; Jurcova, Ivana; Jenca, Dominik; Kroupova, Katerina; Wohlfahrt, Peter; Kotrc, Martin; Melenovsky, Vojtech (JACC. Heart failure, 2025)
BACKGROUND: Growth differentiation factor (GDF)-15 is a pleiotropic cytokine that is associated with appetite-suppressing effects and weight loss in patients with malignancy. OBJECTIVES: This study aims to investigate the relationships between GDF-15 levels, anorexia, cachexia, and clinical outcomes in patients with advanced heart failure with reduced ejection fraction (HFrEF). METHODS: In this observational, retrospective analysis, a total of 344 patients with advanced HFrEF (age 58 ± 10 years, 85% male, 67% NYHA functional class III), underwent clinical and echocardiographic examination, body composition evaluation by skinfolds and dual-energy x-ray absorptiometry, circulating metabolite assessment, Minnesota Living with Heart Failure Questionnaire, and right heart catheterization. RESULTS: The median GDF-15 level was 1,503 ng/L (Q1-Q3: 955-2,332 ng/L) (reference range: <1,200 ng/L). Higher GDF-15 levels were associated with more prevalent anorexia and cachexia. Patients with higher GDF-15 had increased circulating free fatty acids and beta-hydroxybutyrate, lower albumin, cholesterol, and insulin/glucagon ratio, consistent with a catabolic state. Patients with higher GDF-15 had worse congestion and more severe right ventricular dysfunction. In multivariable Cox analysis, elevated GDF-15 was independently associated with risk of the combined endpoint of death, urgent transplantation, or left ventricular assist device implantation, even after adjusting for coexisting anorexia and cachexia (T3 vs T1 HR: 2.31 [95% CI: 1.47-3.66]; P < 0.001). CONCLUSIONS: In patients with advanced HFrEF, elevated circulating GDF-15 levels are associated with a higher prevalence of anorexia and cachexia, right ventricular dysfunction, and congestion, as well as an independently increased risk of adverse events. Further studies are warranted to determine whether therapies altering GDF-15 signaling pathways can affect metabolic status and clinical outcomes in advanced HFrEF.
Keywords: Stroke Volume; Male; retrospektivní studie; srdeční selhání; Weight Loss; Aged; mužské pohlaví; senioři; tepový objem; Cachexia; nechutenství; lidé; ženské pohlaví; Heart Failure; Growth Differentiation Factor 15; Humans; kachexie; hmotnostní úbytek; Retrospective Studies; Anorexia; Female; růstový diferenciační faktor 15; lidé středního věku; Middle Aged